NEWEST TECHNOLOGIES IN THE EDUCATIONAL PROCESSES OF THE INFORMATION SOCIETY - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article investigates The role of the up-to-date information and communication technologies in the educational processes of the Information society are investigated. The attention is drawn to the transformation of the educational process, caused by the informatization processes. The peculiarities of the functioning of the new forms of education such as “open” and “distance” education are primarily discussed.